Reflecting the structural flexibility of public sector institutions in Palestine on the Practice creative behavior. Case study: Ministry of Health- Gaza Strip - Meshmesh, Ashraf Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to show the role of flexible characteristic of the organizational structure (formality degree – central degree – complexity degree) in enhancing the practice of employees for the creative behavior in the Palestinian ministry of health in Gaza strip. This study was conducted on stratified random sample from the employees who work in the supervision positions nearly about (300) employee male/female. A questionnaire was prepared specifically for this purpose and the Statistical analysis has steadied on (267) questionnaires. The study concluded that there is a height of the formality degree – central degree – complexity degree) in the structure of the Ministry of Health in Gaza from the point of view of the study sample. The results of the study reflected that employees in the ministry of health are practicing the creative behaviors in a moderate degree. The results also proved that there is a reverse correlation relationship between the structural flexibility dimensions and enhancing the creative behavior. The results also showed that there is a reverse effect of the degree of complexity dimension on creative behavior, while a formality and central degree are ineffective. One of the most important recommendations in this study is the necessity of decreasing the processes and complexities and emphasizing on the commitment of the policies and regulations, adopting of the policy of delegation, expanding of powers, training on solving problems and supporting ideas and qualitative proposals.